Cognition and motivation forging an interdisciplinary perspective - Kreitler, Shulamith (Cambridge University Press, 2013)
This collection examines the many internal and external factors affecting cognitive processes. Editor Shulamith Kreitler brings together a wide range of international contributors to produce an outstanding assessment of recent research in the field. These contributions go beyond the standard approach of examining the effects of motivation and emotion to consider the contextual factors that may influence cognition. These broad and varied factors include personality, genetics, mental health, biological evolution, culture and social context. By contextualizing cognition, this volume draws out the practical applications of theoretical cognitive research while bringing separate areas of scholarship into meaningful dialogue